Can Other Comprehensive Income Affect Dividend Payments in Indonesia? - Marhaendra Kusuma; Beby Hilda Agustin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
The concept of Other Comprehensive Income (OCI) refers to the difference between the fair value and historical value of assets, resulting from applying fair value principles in financial statement preparation. Despite being unrealized income, it affects equity, and some of its items have a real potential to be realized in the coming period. Previous research has mainly studied the effect of realized income (net income) on dividends, while the impact of unrealized income on dividends, especially in Indonesia, has received limited attention. This study investigates the relationship between OCI and dividends for 682 companies listed on the Indonesia Stock Exchange using data from annual reports spanning from 2015 to 2021. This study employs descriptive statistics, correlation analysis, multiple linear regression analysis, and path analysis to examine the mediating role of profitability and operating cash flows in the relationship between OCI and dividends. The results reveal that OCI, as a whole, does not have a significant impact on dividends. However, when analyzing only the items within OCI that are